Perceptual efficiency and the inversion effect for faces, words and houses. (December 2018) - Albonico, Andrea; Furubacke, Amanda; Barton, Jason J.S.; Oruc, Ipek
Abstract: Face and visual word recognition are two key forms of expert visual processing. In the domain of object recognition, it has been suggested that expert processing is characterized by the use of different mechanisms from the ones involved in general object recognition. It has been suggested that one traditional marker of expert processing is the inversion effect. To investigate whether face and word recognition differ from general object recognition, we compared the effect of inversion on the perceptual efficiency of face and visual word recognition as well as on the recognition of a third, non-expert object category, houses. From the comparison of identification contrast thresholds to an ideal observer, we derived the efficiency and equivalent input noise of stimulus processing in both upright and inverted orientations. While efficiency reflects the efficacy in sampling the available information, equivalent input noise is associated with the degradation of the stimulus signal within the visual system. We hypothesized that large inversion effects for efficiency and/or equivalent input noise should characterize expert high-level processes, and asked whether this would be true for both faces and words, but not houses. However, we found that while face recognition efficiency was profoundly reduced by inversion, the efficiency of word and house recognition was minimally influenced by the orientation manipulation. Inversion did not affect equivalent input noise. These results suggest that even though faces and words are both considered expert processes, only the efficiency of the mechanism involved in face recognition is sensitive to orientation.